2007
DOI: 10.1111/j.1745-7262.2007.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genistein on acrosome reaction and zona pellucida binding independent of protein tyrosine kinase inhibition in bull

Abstract: Our results suggest that in cryopreserved bovine spermatozoa, genistein affects a protein tyrosine phosphorylation-independent signal transduction pathway that is involved in sperm capacitation, the acrosome reaction and sperm-zona pellucida binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…In agreement with these observations, it has been stated that supplementation of a lower EGCG concentration (10 μg/mL) during in vitro fertilization significantly increased fertilization rate, while higher EGCG concentration (25 μg/mL) decreased fertilization rate [ 64 ]. The same observations were reported for ARTs applied for semen/sperm, as high polyphenol levels had detrimental effects on sperm membrane integrity and mitochondrial membrane potential, sperm capacitation, sperm motility, and sperm-zona pellucid binding and thus in vitro fertilization outcomes [ 132 , 135 , 138 , 139 ]. Overall, the action of polyphenols are associated with their chemical structure, level, cell sensitivity, and half-time of reactive oxygen species, which might explain different results obtained following using polyphenolic compounds as antioxidant agents [ 132 ].…”
Section: Polyphenols and In Vitro Assisted Reproduction Techniquessupporting
confidence: 63%
“…In agreement with these observations, it has been stated that supplementation of a lower EGCG concentration (10 μg/mL) during in vitro fertilization significantly increased fertilization rate, while higher EGCG concentration (25 μg/mL) decreased fertilization rate [ 64 ]. The same observations were reported for ARTs applied for semen/sperm, as high polyphenol levels had detrimental effects on sperm membrane integrity and mitochondrial membrane potential, sperm capacitation, sperm motility, and sperm-zona pellucid binding and thus in vitro fertilization outcomes [ 132 , 135 , 138 , 139 ]. Overall, the action of polyphenols are associated with their chemical structure, level, cell sensitivity, and half-time of reactive oxygen species, which might explain different results obtained following using polyphenolic compounds as antioxidant agents [ 132 ].…”
Section: Polyphenols and In Vitro Assisted Reproduction Techniquessupporting
confidence: 63%
“…2) either immediately or one hr after thawing (p > 0.05). These results are in contrast with those of Thomson et al (2009), who found that addition of genistein to the freezing media (100 µM) significantly increased total motility of human sperm, while this effect was not appreciated in bull sperm, not even after 1 hr incubation (Menzel et al, 2007). Taking in account the above data we can suggest that the effect of genistein on sperm motility differs depending on the species used.…”
Section: Py Induction In Frozen-thawed Equine Spermcontrasting
confidence: 91%
“…Besides these differences related to concentration, another question to take into consideration is related to the possible different mechanisms for induced npg capacitation of fresh spermatozoa and cryocapacitation, as previously described in bull spermatozoa [53]. In the frozen bull spermatozoa, the genistein did not affect tyrosine phosphorylation [54], suggesting that cryopreservation affects the regulatory mechanism of capacitation [53,54].…”
Section: Resultsmentioning
confidence: 94%